2019
DOI: 10.3390/ijms20174310
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic BDNF Depletion on GABAergic Synaptic Transmission in the Lateral Amygdala

Abstract: Brain-derived neurotrophic factor (BDNF) has previously been shown to play an important role in glutamatergic synaptic plasticity in the amygdala, correlating with cued fear learning. While glutamatergic neurotransmission is facilitated by BDNF signaling in the amygdala, its mechanism of action at inhibitory synapses in this nucleus is far less understood. We therefore analyzed the impact of chronic BDNF depletion on GABAA-mediated synaptic transmission in BDNF heterozygous knockout mice (BDNF+/−). Analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
(93 reference statements)
1
3
0
Order By: Relevance
“…Nevertheless, BDNF +/− mice displayed neither impaired basal synaptic GABAergic transmission nor altered inhibitory synaptic plasticity in the LA. However, positive modulation of interneuron activity by noradrenaline was significantly decreased by chronic BDNF reduction (Meis et al 2019). In line with these results, BDNF depletion also abolished facilitation of synaptic GABAergic transmission by serotonin (Daftary et al 2012).…”
Section: Cellular Mechanisms Of Amygdala Bdnf/trkb Signalling In Cuedsupporting
confidence: 79%
“…Nevertheless, BDNF +/− mice displayed neither impaired basal synaptic GABAergic transmission nor altered inhibitory synaptic plasticity in the LA. However, positive modulation of interneuron activity by noradrenaline was significantly decreased by chronic BDNF reduction (Meis et al 2019). In line with these results, BDNF depletion also abolished facilitation of synaptic GABAergic transmission by serotonin (Daftary et al 2012).…”
Section: Cellular Mechanisms Of Amygdala Bdnf/trkb Signalling In Cuedsupporting
confidence: 79%
“…During the critical period of sensory system maturation, neuronal activity (due to sensory experience) is likely to be important, not only for the termination of the migration of cortical INs, but also for their proper integration into functional circuits ( de Villers-Sidani et al, 2007 ; Lim et al, 2018 ). There is agreement that an activity-dependent release of BDNF from pyramidal neurons is required to sculpt the integration of the cortical PV-IN network in nearly all sensory cortices, probably by driving cortical tonic inhibition through synaptogenesis of peri-somatic PV-INs with pyramidal neurons ( Hong et al, 2008 ; Xu et al, 2010 ; Griffen and Maffei, 2014 ; Lim et al, 2018 ; Meis et al, 2019 ). The proper integration of GABAergic INs into higher cortical sensory regions is essential for proper feed-forward inhibition, the sharpening of receptive fields, and pattern separation ( Pouille and Scanziani, 2001 ; Leutgeb et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…When BDNF is released from corticostriatal neurons and is bound to the tyrosin kinase tropomyosin-related kinase B receptors, multiple intracellular pathways are activated, as a result of which neurite growth, synaptic plasticity, proliferation, and survival are controlled ( Castrén and Rantamäki, 2010 ; Yoshii and Constantine-Paton, 2010 ). It should be emphasized that BDNF is involved in the maturation of inhibitory GABAergic synapses ( Henneberger et al, 2002 ; Yamada et al, 2003 ; Berghuis et al, 2004 ; Zhu et al, 2019 ), as well as that maturation and functioning of excitatory and inhibitory transmission is also modulated differently by BDNF ( Gottmann et al, 2009 ; Meis et al, 2019 ). Moreover, it has been shown that early NTS treatment leads to increase in the skin and the brain production of FGF-2 ( Richards et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%